Analisis Pengaruh Efek Samping Kemoterapi terhadap Quality of Life Pasien Kanker di RSUD R.A. Kartini - Yahya Adi Alfatih; Eko Retnowati; Intan Adevia Rosnarita (Journal of Innovative and Creativity (Joecy), 2026)
The increasing global cancer incidence has positioned it as a major public health challenge, particularly in Indonesia where chemotherapy remains the primary treatment modality, frequently accompanied by significant side effects that can potentially reduce patient quality of life. This study aimed to analyze the influence of chemotherapy side effects on quality of life among cancer patients at RSUD R.A. Kartini Jepara. An observational analytic study with a cross-sectional design was conducted on 120 cancer patients undergoing chemotherapy in 2025 using purposive sampling. Side effects were measured using the CTCAE v5.0 questionnaire (Cronbach Alpha = 0.882) and quality of life was assessed using the EORTC QLQ-C30 (Cronbach Alpha = 0.994). Chi-Square analysis revealed no statistically significant relationship between chemotherapy side effects and patient quality of life (p = 0.510). The majority of respondents experienced mild side effects (53.9%) with adequate quality of life (75.7%). The most frequently reported side effects were nausea (84.3%), vomiting (77.4%), and diarrhea (59.1%). Patients receiving imatinib mesylate therapy showed the highest proportion of mild side effects. (60.0%), while all cisplatin patients experienced severe effects. These findings suggest that cancer quality of life is influenced by multiple factors beyond chemotherapy toxicity alone, including social support, therapy type, and patient adaptability, necessitating a holistic, patient-centered oncology care approach.